MEASUREMENT AND ANALYSIS OF THE ELECTRICAL PROPERTIES OF REMEDIATED CRUDE OIL IMPACTED SOIL - Ebisine, E. E.; Okieke, U. J.; Oghogho, Ikponmwosa; Oyubu A., Oyubu; Eyenubo, Ogheneakpobo Jonathan; Kevin, Akporhonor Gbubemi (International Journal of Engineering Science Technologies, 2023)
Soil electrical properties are important parameters to be considered during the design of several electrical installations. This study gives an insight into the impact of crude oil contamination on the soil’s electrical behaviors and suitable remediation technique for the contaminated soil. Crude oil was spilled on the soil and this soil was thereafter remediated with poultry (organic) manure and NPK 15:15:15 fertilizer for a duration of 12 weeks; thereafter, some of the soil’s electrical properties (electrical dielectric constant, electrical conductivity and electrical resistivity) were measured in accordance with the Institute of Electrical and Electronic Engineers standard guidelines. Results obtained revealed crude oil had negative impacts on the soil electrical properties; but the remediation agents alleviated these poor electrical properties of the contaminated soil samples. After the remediation programme, the dielectric constant of the contaminated soil treated with 0.5 kg manure (AXT 2) and 1 kg manure (AXT 3) declined by 56.38% and 47.21% respectively; while the contaminated soil treated with 200 g fertilizer (AXT 4) and 400 g fertilizer (AXT 5) declined by 57.49% and 64.54%respectively. The electrical conductivity of AXT 2, AXT 3, AXT 4 and AXT 5 soil samples increased by 46.48%, 50.89%, 32.84% and 41.70% respectively. Furthermore, the AXT 2, AXT 3, AXT 4 and AXT 5 electrical resistivity declined from 1362 Ωm to 579 Ωm, 1362 Ωm to 483 Ωm, 1362 Ωm to 719 Ωm, and 1362 Ωm to 594 Ωm respectively. This study’s revealed the relevance of remediating crude oil contaminated soil to preserve the electrical integrity of electrical installations.